Hepatitis E genotype 4 virus from feces of monkeys infected experimentally can be cultured in PLC/PRF/5 cells and upregulate host interferon‐inducible genes. Issue 10 (11th July 2014) - Zhang, Feng; Qi, Ying; Harrison, Tim J.; Luo, Baobin; Zhou, Yan; Li, Xiuhua; Song, Aijing; Huang, Weijin; Wang, Youchun
<x xml:space="preserve">Abstract</x> The understanding of the interaction between hepatitis E virus (HEV) and its host cells has been impeded greatly by the absence of a cell culture system. In this study, an efficient cultivation method was developed in PLC/PRF/5 cells for HEV genotype 4 from the feces of monkeys infected experimentally. Compared to minimal essential medium (MEM), mixed Dulbecco's Modified Eagle's Medium (DMEM)/M199 improved the infection efficiency of HEV in PLC/PRF/5 cells. The incubation time and temperature were set at 6 hr and 40°C, respectively. Compared to a 100% ELISA positive ratio (EPR) of 1 × 106 copies/ml HEV inoculated flasks, the ELISA positive ratio was 100%, 75%, 37.5%, and 100% for flasks inoculated with HEV incubated for 30 min under the conditions of pH 3.0, pH 11.0, 56°C and delipidation treatment, respectively. Gene expression profiles of HEV inoculated and control PLC/PRF/5 cells were assayed using a microarray. Four interferon‐inducible genes, IFI27, IFI6, Mx1, and CMPK2, were up‐regulated during HEV‐infection. Furthermore, the replication of HEV was inhibited at 3–14 days after treatment with 500 IU/ml IFN‐α2b. J. Med. Virol. 86: 1736–1744, 2014. © 2014 Wiley Periodicals, Inc.